HUBUNGAN ANTARA PEMAHAMAN SEJARAH LOKAL DENGAN SIKAP TOLERANSI MAHASISWA SEJARAH IKIP-PGRI PONTIANAK - Sahid Hidayat; Haris Firmansyah; Fivi Irawani (Khazanah Pendidikan, 2015)
This study aims to determine the relationship between the understanding of local history with tolerance education students history IKIP PGRI Pontianak. The variables in this study are as follows, namely: 1) The independent variables, namely "understanding of local history", 2) The dependent variable, namely "tolerance". The method used in this research is descriptive method, with the form of research studies the relationship. Total population sample of 139 college students and 40 students of fourth semester majoring in history education, data collection techniques used are indirect communication techniques and techniques of documentary studies. Research tool used in the form of a questionnaire. While the data processing techniques used formula r product moment. The conclusion from this study indicate that: "There is a relationship between the understanding of local history with tolerance education students history IKIP PGRI Pontianak ". The conclusion is evident in the calculation of the data shows that there is a relationship of 0.822 with the category of "Very Strong". Keywords: local history, tolerance